Sustaining Threat Narratives about Muslims and Arabs in Germany in The Post 9/11 Era: An Analysis of Showtime?s Homeland - Abass, Khadija (Department of Sociology, 2024)
Twenty years after 9/11 and Islamophobia is still on the rise as evidenced by the increased securitisation of Muslims in the form of immigration laws, anti-terror legislation, and restrictions on religious freedoms. My hypothesis is that televisual texts play a major role in the cultural production of knowledge and that threat narratives about Muslims are particularly sustained through texts belonging to the Dark Americana genre which foregrounds emotional complexity, security challenges, and moral ambivalence regarding the state's use of violence and surveillance. Reception analysis requires insight into the televisual text, the sociocultural characteristics of the viewer, and the socio-political context of the time. Consequently, my research balances theoretical reflections on Homeland's ability to sustain threat narratives, according to Bordwell's Three Dimensions of Film (2008), with an empirical study on the show's reception by university students in Germany. My qualitative analysis paid special attention to the textual features of the show and interrogated how meaning arises from cinematic techniques. It found that close-up shots are particularly effective for constructing emotion in audiences and produces sympathy and relatability, potentially serving to justify characters' questionable behaviour in the eyes of the audience. I synthesised three methodologies for my reception analysis. I used online surveys to obtain data about participants' sociocultural characteristics and the Minutia Reception Method to measure participants' moment-by-moment engagement with the text. The ‘Grounded Theory Coding Approach' and follow-up emails then allowed me to systematically create categories based on repeated themes prevalent in the data sample. As a result, I have added four new sub-narratives to the Dark Americana genre, including the Reimagination of US Nationalism, the use of Moral Panic to create Moral Ambiguity around state violence, an ‘us versus them' dichotomy that ensures that the west's violence is considered Heroism while the violence of the ‘other' is considered Extremism, and imperial feminism which disguises western violence. While the Dark Americana genre, a concept developed by David Martin Jones and M.L.R. Smith, supposedly questions state violence, my analysis of Homeland season one found that it reinforces justifications for state violence and sustains threat narratives about Muslims and Arabs in the post 9/11 era through the distinct sub-narratives which I have introduced.